2022
DOI: 10.1111/jonm.13804
|View full text |Cite
|
Sign up to set email alerts
|

Nursing perspectives on transitional care between paediatric intensive care units and general wards: A focus group study

Abstract: Aim: We aim to explore the experiences of nursing staff in paediatric intensive care units (PICUs) and wards when transporting and caring for patients being discharged from PICU.Background: PICU discharge is a challenging and complex procedure with risks and complications for patients. Nursing staff in PICU and paediatric wards play a pivotal role in the transition and are responsible for the quality of care, but their perspectives have rarely been explored.Methods: Focus groups were conducted between December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Several doctors in the present study reported that decisions about transferring children are made jointly by nurses and doctors based on their condition. However, a preliminary study found that nurses were rarely be able to take part in the decision-making process for transfer [9] , which aligns with ndings from other studies [26,30,31] .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Several doctors in the present study reported that decisions about transferring children are made jointly by nurses and doctors based on their condition. However, a preliminary study found that nurses were rarely be able to take part in the decision-making process for transfer [9] , which aligns with ndings from other studies [26,30,31] .…”
Section: Discussionsupporting
confidence: 84%
“…Examining different viewpoints on the challenges and facilitators can unveil novel insights into enhancing the PICU-to-ward transition, which ultimately leads to better patient care [27] . In previous studies [8][9][10][11]29] , while previous research has explored parents' and nurses' perspectives on transitional care, doctors' views have not been thoroughly investigated. The aim of this research is to identify shortcomings in the delivery of transition care by understanding the perspectives of doctors, which will then have implications for the provision of appropriate training curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several doctors in the present study reported that decisions about transferring children are made jointly by nurses and doctors based on their condition. However, a preliminary study found that nurses were rarely be able to take part in the decision-making process for transfer, 9 which aligns with findings from other studies. 26 , 30 , 31 Regarding shared decision-making, there is currently a lack of awareness among doctors.…”
Section: Discussionsupporting
confidence: 81%
“…SEHOP is an effectiveness and efficiency indicator that should accompany every PICU patient on discharge including standardized documentation of the reasons for admission and the forthcoming diagnosis made, the on-going problems, the full list of the recent medications and alterations of previous if any, and the issues that need to be resolved [23][24][25][26]. The diagnosis should follow a recognized system of classifying disease and the information should be available to all clinical teams caring for the patient post discharge.…”
Section: Standardized Electronic Handover Procedures (Sehop) For Disc...mentioning
confidence: 99%